Dexamethasone and zinc loaded polymeric nanoparticles reinforce and remineralize coronal dentin. A morpho-histological and dynamic-biomechanical study. Issue 1 (January 2023) - Toledano, Manuel; Osorio, Estrella; Aguilera, Fátima S.; Osorio, María T.; Toledano, Raquel; López-López, Modesto T.; Lynch, Christopher D.; Osorio, Raquel
Abstract: Objective: To investigate the effect of novel polymeric nanoparticles (NPs) doped with dexamethasone (Dex) on viscoelasticity, crystallinity and ultra-nanostructure of the formed hydroxyapatite after NPs dentin infiltration. Methods: Undoped-NPs, Dex-doped NPs (Dex-NPs) and zinc-doped-Dex-NPs (Zn-Dex-NPs) were tested at dentin, after 24 h and 21 d. A control group without NPs was included. Coronal dentin surfaces were studied by nano-dynamic mechanical analysis measurements, atomic force microscopy, X-ray diffraction and transmission electron microscopy. Mean and standard deviation were analyzed by ANOVA and Student-Newman-Keuls multiple comparisons (p < 0.05). Results: At 21 d of storage time, both groups doped with Dex exhibited the highest complex, storage and loss moduli among groups. Zn-Dex-NPs and Dex-NPs promoted the highest and lowest tan delta values, respectively. Dex-NPs contributed to increase the fibril diameters of dentin collagen over time. Dentin surfaces treated with Zn-Dex-NPs attained the lowest nano-roughness values, provoked the highest crystallinity, and produced the longest and shortest crystallite and grain size. These new crystals organized with randomly oriented lattices. Dex-NPs induced the highest microstrain. Crystalline and amorphous matter was present in the mineral precipitates of all groups, but Zn and Dex loaded NPs helped to increase crystallinity. Significance: Dentin treated with Zn-Dex-NPs improved crystallographic and atomic order, providing structural stability, high mechanical performance and tissue maturation. Amorphous content was also present, so high hydroxyapatite solubility, bioactivity and remineralizing activity due to the high ion-rich environment took place in the infiltrated dentin. Graphical Abstract: Graphical abstract summarizing the study design. ga1 Highlights: Dentin treated with Zn-Dex-NPs showed low levels of accumulated energies over time. Dex-NPs and Zn-Dex-NPs in conditioned dentin promoted functional remineralization. Dentin treated with Zn-Dex-NPs showed the highest crystallinity and low amorphization. Dentin with Zn-Dex-NPs exhibited less spaced random and compacted nanocrystals.